Teacher education in Bolivia: two visions and new perspectives (Praxis Educativa, 2015)
Values and sense of teacher education have experienced vision changes within the last educational reforms in Bolivia. These structural reforms adopted different curricular concepts, they settled pedagogical knowledge as a practical knowledge and differentiated importance was granted to disciplinary knowledge and research. If there is a guiding element in both approaches of teacher education, it is the emphasis on the recognition of cultural diversity and the importance of teaching practice as the axis of the learning process. The current reform puts a special emphasis on symmetrical and horizontal relations between the country’s own cultures and Western culture. The emergence of diversity in Bolivia makes a commitment to diversity of knowledge or science and the diversity of ways of knowledge. It is a different perspective on current Colleges of Teacher Education.
Keywords: teacher education; curriculum; diversity; research